w+6=57

Simple and best practice solution for w+6=57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w+6=57 equation:


Simplifying
w + 6 = 57

Reorder the terms:
6 + w = 57

Solving
6 + w = 57

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + w = 57 + -6

Combine like terms: 6 + -6 = 0
0 + w = 57 + -6
w = 57 + -6

Combine like terms: 57 + -6 = 51
w = 51

Simplifying
w = 51

See similar equations:

| 24v^4w^9-18vw^3y^5= | | 5x?5x= | | 693950=.798750X | | 693950=.798750 | | 8xy-9x= | | 400x+36000=2000x+12000 | | y=5/6(126) | | 5/6-1/3n=5p-2np | | 1-2x=6-4x | | 4X-2.5=7.4 | | 7b-16=-45 | | .08X=700 | | 7-(3n-8)=-6 | | 7x^2+3=5 | | -10+9x=12 | | -x+6y=-1 | | 6-(2)(3)= | | 0.4(2x-0.5)=3[0.2x-(-2)]-4 | | 9x^2-3x-45=0 | | -3(5x+3)=-144 | | 1=3b | | 18-12n=16+3n-11 | | 4m=256 | | simplify5/13(75-49) | | 3(4x+5)=-5+53 | | 4m=156 | | 12+6x-3x=30 | | (x+1)[2(3x-1)-(4+5x)]=2(x-1)(x+2)+4 | | 0.2=-1.2n-7 | | Y=-2(-6)+4 | | -8(z-9)=3-7z | | -9(-6v+y-3)= |

Equations solver categories